PENGGUNAAN METODE MATERNAL REFLEKTIF (MMR) UNTUK MENINGKATKAN KEMAMPUAN BERBICARA ANAK TUNARUNGU DI TK SLB PANGUDI LUHUR - Lathipah Hasanah (LP2M IAIN Sultan Amai Gorontalo, 2022)
Children with hearing impairement have difficulty communicating because of the language limitations so they will use sign language to communicate. Reflective Maternal Method (MMR) is one of the teaching methods that are expected to develop language skills especially for children with hearing impairment so it can communicate using oral language. The main focus of the study consisted of: (1) How the children speech ability and (2) How is the procedure of using Reflective Maternal Method (MMR). The research method used literature study and field study by observing the learning process in the class of children with hearing impairement using the Reflective Maternal Method (MMR). This research involves children with age range 6-8 years in SLB Pangudi Luhur Kindergarten, Jakarta which consists of 12 people. To illustrate the situation that occurred in the subject of research, this study used a qualitative approach. Research data collected in the form of observation, interview, and documentation data. From the results of this study, it is known that the Reflective Maternal Method (MMR) have a role in developing speech skills in children with hearing impairment. Based on the results of field studies, it can be described that the use of Reflective Maternal Method (MMR) in SLB Pangudi Luhur includes the following stages: (1) Preparation, (2) Integrated Speech, (3) Week Board, (4) Conversation, (5) Visualization, (6) Visualization Processing, (7) Copy visualization, and (8) Reading speech utterance. Keywords: Reflective Maternal Method (MMR), Speech Ability, Children with Hearing Impairement